Determinación de los contaminantes producto de la combustión del parque automotor a gasolina en la parroquia Ignacio Flores, ciudad de Latacunga, período 2015 - Cortez Villacis, Miguel Ángel (2016)
This thesis has given a vision of vehicular pollution generated by gasoline vehicle fleet in Latacunga city Ignacio Flores. Panish describes the environmental and human health problems caused by vehicular pollution because of excessive increase in the last decades to the automobite fleet; which it mentioned some air pollutants are outlined and what the major pollutants emitted by the vehicle fleet such as carbon monoxide (CO) and hydrocarbons (HC) affecting the average, according to this problema, the monitoring was carried out of gaseous pollutants from vehicles with AVL DITEST 1000 team that helped to lift a database of emissions emanating from the vehicle fleet gasolina, according to the permissible limits for gas emissions as gasoline vehicles Ecuadorian Technical Standard NTE INEN 2204: 2002, compared to the corresponding measurements in the vehicles. After take up and compare gas monitoring data in Ignacio Flores parish it has analyzed the current situation and determined marked redueed strategies of pollution from the automobile Fleets….